2012
DOI: 10.1016/j.neuron.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Proteolytic Cleavage of Neuroligin-1

Abstract: Neuroligin (NLG), a postsynaptic adhesion molecule, is involved in the formation of synapses by binding to a cognate presynaptic ligand, neurexin. Here we report that neuroligin-1 (NLG1) undergoes ectodomain shedding at the juxtamembrane stalk region to generate a secreted form of NLG1 and a membrane-tethered C-terminal fragment (CTF) in adult rat brains in vivo as well as in neuronal cultures. Pharmacological and genetic studies identified ADAM10 as the major protease responsible for NLG1 shedding, the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
227
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(244 citation statements)
references
References 75 publications
(105 reference statements)
16
227
1
Order By: Relevance
“…This indicated MMP and ADAM family proteases as candidate enzymes, a prediction consistent with the reported enzyme(s) responsible for Nlgn1 cleavage 17,18 and neural ADAM10 targets 19 . Active slice CM generated in the absence and presence of various protease inhibitors exhibited decreased neuroligin-3 shedding with MMP9 and ADAM10 inhibitors (Fig.…”
supporting
confidence: 85%
“…This indicated MMP and ADAM family proteases as candidate enzymes, a prediction consistent with the reported enzyme(s) responsible for Nlgn1 cleavage 17,18 and neural ADAM10 targets 19 . Active slice CM generated in the absence and presence of various protease inhibitors exhibited decreased neuroligin-3 shedding with MMP9 and ADAM10 inhibitors (Fig.…”
supporting
confidence: 85%
“…In addition, in B6 mice, synaptic NLG1 protein level was also decreased by SD in the anterior forebrain, which could be more representative of NLG1 with B, given the absence of changes for the other variants. Indeed, recent data indicate that neuronal activity decreases NLG1 level at the synapse (25,42), and our findings suggest that this decrease mainly concerns the isoform containing insert B. NLG1 with B, the expression of which in the brain prevails over isoforms lacking B (19), is mostly localized at glutamatergic synapses and is specifically implicated in the interaction with presynaptic Neurexins (NRX) (19,29). Studies have shown that proper NMDAR function requires both the presence of NRX and NLG (21,43,44).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, it could facilitate synaptic disassembly. For example, removal of transsynaptic ligands by proteolytic cleavage, as recently reported for neuroligin-1 (Peixoto et al, 2012;Suzuki et al, 2012) and NGL-3 , might rapidly reduce the affinity of cis interactions and trigger the disassembly of adhesion protein complexes.…”
Section: Discussionmentioning
confidence: 87%